2005
DOI: 10.1113/jphysiol.2005.097022
|View full text |Cite
|
Sign up to set email alerts
|

Differential targeting and functional specialization of sodium channels in cultured cerebellar granule cells

Abstract: The ion channel dynamics that underlie the complex firing patterns of cerebellar granule (CG) cells are still largely unknown. Here, we have characterized the subcellular localization and functional properties of Na + channels that regulate the excitability of CG cells in culture. As evidenced by RT-PCR and immunocytochemical analysis, morphologically differentiated CG cells expressed Nav1.2 and Nav1.6, though both subunits appeared to be differentially regulated. Nav1.2 was localized at most axon initial segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 50 publications
(64 reference statements)
2
49
0
Order By: Relevance
“…Consistent with previous work, ankyrin G (Ank G ) and Na v 1.6 were strongly coexpressed at the AIS in 14 DIV WT CGNs (Fig. 4A) (31,35). In contrast, the proportion of Ank G -positive AIS expressing Na v 1.6 was reduced in Scn1b null CGNs (P < 0.001; Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with previous work, ankyrin G (Ank G ) and Na v 1.6 were strongly coexpressed at the AIS in 14 DIV WT CGNs (Fig. 4A) (31,35). In contrast, the proportion of Ank G -positive AIS expressing Na v 1.6 was reduced in Scn1b null CGNs (P < 0.001; Fig.…”
Section: Resultssupporting
confidence: 80%
“…This may hinder the ability to detect any alteration in axonal VGSC expression in Scn1b null CGNs in vivo (30,31). As in dissociated CGNs, transient I Na was unchanged in 14 DIV Scn1b null CGNs (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Under current-clamp conditions, CGCs of 7-11 days in vitro showed negative resting potential (À63 AE 2 mV, n ¼ 5), and spontaneous synaptic inputs in the form of bursting patterns as previously described [Becherer et al, 1997;Osorio et al, 2005], usually observed once or twice over a 2 min recording interval. Bath application of 10 mM gambierol did not affect the resting membrane potential of CGCs; however, it caused small oscillation of the membrane potential and repetitive firing (Fig.…”
Section: Effect Of Gambierol On Sodium and Potassium Currents In Cerementioning
confidence: 91%
“…For voltage-dependent sodium channels voltage-gated ion currents were elicited in CGCs by applying a series of 25 ms depolarizing pulses (voltage steps), in 5 mV increments, from a holding potential of À100 mV [Osorio et al, 2005]. Current-voltage (I-V) relationship for transient, voltage-gated sodium currents were obtained by measuring the peak amplitude of the current for each given membrane potential during the voltage steps.…”
Section: Electrophysiologymentioning
confidence: 99%
“…In vitro studies have demonstrated that the Na v 1.2 subunit encoded by Scn2a localizes to the axon initial segment in cerebellar granule cells [267] and that pharmacological modulation of voltage-gated sodium channel activity in cortical neurons influences neurite length and complexity as well as density of spines and excitatory synapses [123, 124]. Alternative splicing of Scn2a results in differential expression of the various isoforms during development and adulthood [121], possibly as a means of controlling neuronal excitation.…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%